LIN‐28 balances longevity and germline stem cell number in Caenorhabditis elegans through let‐7/AKT/DAF‐16 axis. Issue 1 (11th October 2016) - Wang, Dan; Hou, Lei; Nakamura, Shuhei; Su, Ming; Li, Fang; Chen, Weiyang; Yan, Yizhen; Green, Christopher D.; Chen, Di; Zhang, Hong; Antebi, Adam; Han, Jing‐Dong J.
Summary: The RNA‐binding protein LIN‐28 was first found to control developmental timing in Caenorhabditis elegans . Later, it was found to play important roles in pluripotency, metabolism, and cancer in mammals. Here we report that a low dosage of lin‐28 enhanced stress tolerance and longevity, and reduced germline stem/progenitor cell number in C. elegans . The germline LIN‐28 ‐ regulated microRNA let‐7 was required for these effects by targeting akt‐1/2 and decreasing their protein levels. AKT‐1/2 and the downstream DAF‐16 transcription factor were both required for the lifespan and germline stem cell effects of lin‐28 . The pathway also mediated dietary restriction induced lifespan extension and reduction in germline stem cell number. Thus, the LIN‐28/let‐7/AKT/DAF‐16 axis we delineated here is a program that plays an important role in balancing reproduction and somatic maintenance and their response to the environmental energy level—a central dogma of the 'evolutionary optimization' of resource allocation that modulates aging.